Pre-adaptative and adaptative management of multimorphic cancer pain: the keys to optimizing the patient's journey - Fulcrand, Julie; Dewaele, Hélène; Gourcerol, Guillaume; Scotté, Florian; Dupoiron, Denis; Burnod, Alexis; Lemaire, Antoine (Frontiers in Pain Research, 2025)
The number of patients living with cancer has increased and their management has dramatically changed, resulting in major survival improvement. Thus a new paradigm arose with a focus not only on cancer treatments but also on maintenance of the best possible quality of life. Cancer pain is frequent and remains insufficiently relieved, highlighting the gap between theory and real life, scientific skills, and their application. Cancer pain is multimorphic, complex, multifaceted, and changes over time from diagnosis until cure or palliative situations. These modifications result from the interaction of intrinsic and extrinsic factors that create disruptions along the cancer care pathway. Pain screening must be systematic, and performed by any healthcare professional in contact with cancer patients at any time, in any context. Pain management must be individualized and adapted to each patient, anticipated whenever possible by identifying disruptive factors. The classical stepwise process should be abandoned in favor of an integrated model where supportive care and, in particular, pain management, is an integral part of cancer care from diagnosis to survivorship. Interdisciplinary management is necessary, requiring efficient teamwork led by a conductor. As supportive care plays a key role, it must be implemented in an early and timely manner, taking into account different aspects of the patient's life including physical, psychological, social, and spiritual aspects.